Immune checkpoint inhibition and targeted therapy for melanoma: a patient-oriented cross-sectional comparative multicentre study - Thiem, Alexander; Mashhadiakbar, Pegah; Cussigh, Christiane; Hassel, Jessica C.; Grimmelmann, Imke; Gutzmer, Ralf; Schlaak, Max Simon; Heppt, Markus V.; Dücker, Pia; Hüning, Svea; Schulmeyer, Lena; Schilling, Bastian; et al. (Journal of the European Academy of Dermatology and Venereology, 2023)
Background Choosing the adequate systemic treatment for melanoma is driven by clinical parameters and personal preferences. Objective Evaluation of the impact of disease and treatment on the daily life of patients receiving systemic therapy for melanoma. Methods A German-wide, cross-sectional comparative study was conducted at 13 specialized skin cancer centres from 08/2020 to 03/2021. A questionnaire was distributed to assess patients' perception of disease and symptoms, the impact of their current treatment on quality of life (QOL) and activities, adverse events (AEs), therapeutic visits, as well as believe in and satisfaction with their current systemic melanoma treatment. Patient-reported outcomes (PROs) were rated on a continuous numerical rating scale or selected from a given list. Results Four hundred and fourteen patients with systemic melanoma therapy were included. 359 (87%) received immune checkpoint inhibition (ICI) and 55 (13%) targeted therapy (TT). About 1/3 of patients were adjuvantly treated, the remaining because of unresectable/metastatic melanoma. In subgroup analyses, only in the adjuvant setting, TT patients reported a significant decrease in their treatment associated QOL compared to patients with ICI (p = 0.02). Patients with TT were 1.9 times more likely to report AEs than patients with ICI, a difference being significant just for the adjuvant setting (p = 0.01). ICI treatment intervals differed significantly between adjuvant and unresectable/metastatic setting (p = 0.04), though all patients, regardless of their specific ICI drug, evaluated their treatment frequency as adequate. TT patients with dabrafenib/trametinib (n = 37) or encorafenib/binimetinib (n = 15) did not differ regarding the strain of daily pill intake. Patients older than 63 years rated various PROs better than younger patients. Conclusions Patients evaluated their treatment mainly positively. ICI might be preferred over TT regarding QOL and patient-reported AEs in the adjuvant setting. Older melanoma patients appeared to be less impacted by their disease and more satisfied with their treatment.
Gesehen am 30.07.2024
Erstmals veröffentlicht: 25. November 2022